HOW CLEAR ALIGNER PERFORMED IN TREATING CLASS I, II, III MALOCLUSION? A RETROSPECTIVE STUDY - Mohammed Barashi (Romanian Journal of Oral Rehabilitation)
Aim of the study: This research aims to evaluate the performance of clear aligners in treating Class I, Class II, and Class III malocclusion. Materials and methods: The study retrospectively assessed healthy adult patients treated orthodontically with clear aligners. Data analysis included descriptive statistics, chi-square tests, and regression analyses to assess the relationships between Angle's classifications, spacing or crowding measurements, and the need for treatment refinement. Results: Participants comprised a total of 115 individuals, including a female majority (87.0%; n=100). The data presents the distribution of cases according to the Angle classification among the participants. Class I cases comprise the majority at 57.4% (n=66), followed by Class II at 27.8% (n=32), and Class III at 14.8% (n=17). The coefficient is 0.64, suggesting that individuals in Class III have a mean spacing or crowding at the end of treatment that is significantly greater than those in Class I, with a statistically significant p-value (<0.01; 95% CI: 0.29, 0.99). Conclusions: This study indicates that clear aligners might be more effective for treating Class I malocclusion, while Class II and III cases require more adjustments. Further research is necessary to understand the long-term effects of clear aligners and to optimize treatment strategies for different types of malocclusions.